An asset value evaluation for docking finance lease problems in the peer-to-peer platform - Qu, Jiang; Liu, Hongwei; Zhu, Hui; Gao, Hongming (Journal of Business Economics and Management, 2021)
The convenience and rapidity of financial leasing modes in the peer-to-peer (P2P) platform enable small and medium-sized enterprises (SMEs) to solve financing problems. The core of risk management in the P2P platform is to improve the quality of the docking assets. Therefore, the purpose of this paper is to establish a financial leasing value model of debt cession with an optimal economic pattern and an analysis of the risk assessment to improve the management of the asset value docking quality of both parties. For the transaction price of the leased assets in a P2P platform, this paper establishes multi-periodic, continuous, and variable models of the leased assets value evaluation, taking rent, lease term, and interest as independent variables. The paper proves that the price of the leased assets is related to the interest force, the rent per period, and the numbers of payments and changes in rent when other factors remain unchanged. Our results prove that the risk of the P2P platform docking finance lease and the transfer of the creditor’s rights investment mode are low. The proposed scheme is verified through hypothesis testing and model simulation. When the lease term is longer and the interest rate is higher, the difference between the two function surfaces is larger. Thus, the business model of financial leasing in the P2P platform has more obvious business advantages. It provides better business macro direction and business micro-management guidance for the leasing industry, P2P platforms and financial leasing companies.First published online 21 December 2020